(untitled) (Biological Sciences - PJSIR, 1998)
High molecular weight acid phosphatase from chicken liver was purified by salt fractionation, gel filtration on Sephadex G-150 and by affinity chromatography on Sepharose4B-L-Tartramicamide column. The purified enzyme moved as a single band. The molecular weight was estimated to be approximately 100 k.Oa. by gel filtration on SephadexG-l 00andapproximately50k.Oa.by SOSpolyacrylamidegelelectrophoresisindicatingdimericprotein.K, againstp-nitrophenyl phosphate and phenyl phosphate at pH 5.0 and ionic strength 0.15 were found to be 0.08 mM and 0.12mM respectively, while the Vmax for these two substrates were 275 Umin’ mg’ and 250 Umin’ mg! of protein respectively. The enzyme was strongly inhibited by phosphate, tartrate, vanadate and molybdate. The ideal substrates for the enzyme were4-ethyl phenyl phosphate,4-trifluoromethy-phenyl phosphate, a-naphthyl phosphate and o-phosphotyrosine in addition to p-nitrophenyl phosphate and phenyl phosphate. Other substrates were also hydrolysed but at slower rates.